Rural areas in transition: Village development in the light of new structures of responsibility - Zora Becker (Spatial transformation: Processes, strategies, research design, 2022)
This article focuses on the challenges of rural areas, the formative power of citizens and the funding programme for village development in Lower Saxony. The article elaborates the importance of collective responsibility in villages by means of cooperation between local political representatives, the administration and village residents in their various functions. It points out the need for further research on the assumption of responsibility; using the example of the funding programme for village development in Lower Saxony, the article pursues options for methodically supporting these processes in future.
urn:nbn:de:0156-08911233; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Village development; responsibility; participation; civic engagement; planning process; rural areas